PENERAPAN UNSUR TINDAK PIDANA PENCUCIAN UANG YANG BERASAL DARI HASIL TINDAK PIDANA NARKOTIKA PADA TINGKAT PENYIDIKAN (Studi Pada BNNP dan Ditresnarkoba Polda Sumbar) - Kusnedi, Kusnedi (Universitas Ekasakti, 2020)
The crime of money laundering does not stand alone because the assets placed by integration are obtained from a crime. The investigator has the authority to submit an application to the District Court so that the court decides assets that are known or reasonably suspected to be the result of narcotics crime being assets of the State or returned to those entitled under Article 137 letter (a) of Law Number 35 Year 2009 regarding Narcotics, Article 3, 4, and 5 paragraph (1) of Law Number 8 of 2010 concerning the prevention and eradication of criminal acts of laundering. This has an impact on pinyidik ​​at BNNP and the Directorate the West Sumatra Regional Police in proving the element of money laundering which is allegedly the result of narcotics crime. Application of elements of laundering money derived from proceeds of crime, narcotics based on Article 137 (a) Law of the Republic of Indonesia Number 35 Year 2009 on Narcotics, Articles 3, 4, and 5, paragraph (1) of the Act Republic of Indonesia Number 8 Year 2010. Constraints are faced by investigators BNNP namely: a) Constraints internal factors, and b) constraint factors external. Efforts were made to overcome the obstacles by the investigation BNNP, namely: a) attempts to overcome internal factor constraints faced by investigators BNNP in combating money laundering based narcotic crime, and b) the efforts made to overcome external factor constraints by BNNP investigators in eradicating money laundering which is based on narcotics crime.